TESTICULAR LIPOMATOSIS IN COWDEN DISEASE - Khan, Dawar; Memon, Wasim A; Siddiqui, Saad (Journal of Ayub Medical College Abbottabad, 2015)
Cowden disease is a genetic syndrome resulting in formation of multiple premalignant hamartomas in different parts of the body with classical radiological features. In this report a case of Testicular Lipomatosis as a result of Cowden disease resulting in primary infertility.